PENGARUH LAMA DAN INTERVAL ISTIRAHAT TERHADAP PRODUKTIVITAS PEKERJA - , MAHRUS KHOIRUL UMAMI, Ir. Subagyo, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rest-break is one of important factors in scheduling of work hours. Restbreak scheduling can be performed based on the time needed by the body to recover from physical and mental fatigue. In scheduling of rest-break, the productivity of workers must also be considered. In this study an assessment is conducted on the workers productivity as a result of some work-rest schedules that have been defined. Experiments carried out on two tasks, computer task, i.e. word processing, and assembling-disassembling task with Tamiya as an object. The computer task is performed using Microsoft Office Word 2007 program on Windows XP Professional operating system. The subjects participated on the experiment of this study were 14 persons, consist of 7 males and 7 females. Productivity on the computer work is determined based on the number of words typed correctly per minute, whereas the productivity on assembly-disassembly task is determined based on the number of cycles completed by the subjects. In this study, five workrest schedules were investigated: 5 minutes break - 60 minutes work, 5 minutes break - 120 minutes work, 15 minutes break - 60 minutes work, 15 minutes break - 120 minutes work, and 240 minutes of continuous work without rest. Statistical analysis was performed using two-way analysis of variance and one-way analysis of variance. Two-way analysis of variance was used to test the effect of rest duration, rest intervals, and the interaction of both on the productivity. One-way analysis of variance was used to test whether there were some differences in worker productivity caused by the implementation of the fifth schedules. The results of this study indicate that no significant impact of rest duration, rest intervals, and the interaction of both on subjects productivity on the word processing task using computer and assembling-disassembling task. The results also showed that the implementation of the fifht schedules had no significant impact on subjects productivity. Thus, it can be stated that the granting of scheduled rest did not affect the workers productivity on computer task and Tamiya assembling-disassembling task.